2004
DOI: 10.1016/j.precamres.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Ediacaran chronostratigraphy, Wernecke Mountains, northwestern Canada

Abstract: Terminal Neoproterozoic (Ediacaran, ca. 600-543 Ma) strata of the upper part of the Windermere Supergroup are well-exposed in the Mackenzie Mountains and the Wernecke Mountains of northwestern Canada. Windermere strata in the Mackenzie Mountains contain an exceptional Ediacaran biostratigraphic and isotopic (C and Sr) record, while the sequence stratigraphic record is subtle throughout this predominantly deep-water succession. Coeval strata in the Wernecke Mountains can be correlated with the succession in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 69 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Remarks.-The specimen in Figure 3.8 is a discoid fossil preserved in convex hyporelief, the normal preservation for specimens of Aspidella previously described from the Blueflower Formation (Narbonne and Aitken, 1990;MacNaughton et al, 2000;Pyle et al, 2004) and elsewhere worldwide (Gehling et al, 2000;Fedonkin et al, 2007). Discoid fossils preserved as raised features on bed soles (convex hyporeliefs) are the most abundant fossils of the Ediacara biota, and formerly were described under a wide array of taxonomic names.…”
Section: Genus Aspidella Billings 1872mentioning
confidence: 75%
See 1 more Smart Citation
“…Remarks.-The specimen in Figure 3.8 is a discoid fossil preserved in convex hyporelief, the normal preservation for specimens of Aspidella previously described from the Blueflower Formation (Narbonne and Aitken, 1990;MacNaughton et al, 2000;Pyle et al, 2004) and elsewhere worldwide (Gehling et al, 2000;Fedonkin et al, 2007). Discoid fossils preserved as raised features on bed soles (convex hyporeliefs) are the most abundant fossils of the Ediacara biota, and formerly were described under a wide array of taxonomic names.…”
Section: Genus Aspidella Billings 1872mentioning
confidence: 75%
“…Most Ediacaran body fossils and trace fossils from the Mackenzie Mountains are from slope deposits (Dalrymple and Narbonne, 1996;MacNaughton et al, 2000;Macdonald et al, 2013;Narbonne et al, 2014;Carbone and Narbonne, 2014), although shallow-water deposits at the top of the Blueflower Formation have yielded single specimens of the probable dickinsonid Windermeria Narbonne, 1994 and an Ediacaria-morph of the holdfast disc Aspidella Billings, 1872 (Narbonne and Aitken, 1990), along with a low diversity assemblage of mainly simple, sub-horizontal burrows (Carbone and Narbonne, 2014). Shallow-water equivalents of the Blueflower Formation in the Wernecke Mountains, 250 km west-northwest of Sekwi Brook (Pyle et al, 2004), have yielded abundant Ediacara-type discoid body fossils and simple trace fossils along with a single specimen of the Ediacaran frond Charniodiscus Ford, 1958(Hofmann et al, 1983Narbonne and Hofmann, 1987;Pyle et al, 2004), and were previously cumulatively considered the only Ediacaran shallow-water assemblage from NW Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations of the Wernecke Mountains have led to the identification of an Ediacaran mixed siliciclastic and carbonate succession that records the transition from inner shelf or platform to slope facies along a present-day north-to-south transect, specifically from the Goz/Corn Creek area (proximal or shallow water) to the Nadaleen River region (distal or deep water) (Busch et al, 2022(Busch et al, , 2023Macdonald et al, 2013;Moynihan et al, 2019;Pyle et al, 2004) (Figure 1). The Ediacaran succession stratigraphically overlies Marinoan glaciogenic strata of the Ice Brook Formation and the informal Ravensthroat cap carbonate (James et al, 2001;Macdonald et al, 2013Macdonald et al, , 2018Moynihan et al, 2019), which has been recently formalized as the Cliff Creek Formation (Busch et al, 2021).…”
Section: Geological and Paleontological Backgroundmentioning
confidence: 99%
“…dolostone. In some areas, this carbonate has been identified as the Gametrail Formation (Narbonne, 2005;Pyle et al, 2004), but recent work suggested it rests gradationally upon the Sheepbed Formation and is referred to informally as the "Sheepbed carbonate" (Busch et al, 2023;Macdonald et al, 2013). At the shallowest-water Goz A section (Figure 5), the Sheepbed carbonate is capped by a subaerial karstic unconformity and overlain by interbedded shale, sandstone, and carbonate of the Nadaleen Formation (Macdonald et al, 2013) (note the Nadaleen Formation was previously referred to as the "June Beds" by Macdonald et al (2013) before its formalization by Moynihan et al (2019)).…”
Section: Geological and Paleontological Backgroundmentioning
confidence: 99%
“…However, these geochemical features of the basal Cambrian change 17 upwards to more evolved compositions with lower  Nd (t) values (-4.9 to -5.8 Worldwide, the Ediacaran-Cambrian boundary corresponds to a major unconformity in 27 most sections, suggesting a possible eustatic fall in sea level (Bartley et al 1998; Saylor 28 2003;Knoll et al 2004;Pyle et al 2004 Thomas et al 2004;Soulaimani et al 2004; 42 Álvaro et al 2010). 43…”
mentioning
confidence: 99%